1988
DOI: 10.1139/y88-130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desmodium adscendens fractions on antigen- and arachidonic acid-induced contractions of guinea pig airways

Abstract: Three fractions (n-butanol, F2, and L5), isolated from an aqueous extract of Desmodium adscendens, a plant used in Ghana for the management of asthma, were evaluated for their pharmacological activity using ovalbumin and arachidonic acid-induced contractions of guinea pig airways. All three fractions inhibited the ovalbumin-induced contractions of indomethacin-pretreated tracheal spirals from sensitized animals dose dependently, but only L5 and n-butanol inhibited such contractions in the absence of indomethac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Several studies have been carried out to verify if the plant relaxes smooth muscle and to understand better its action. It has been suggested that the action mechanism of the plant is due to the depletion of the HST stocks (Addy and Awumey, 1984); the inhibition of the cyclooxygenase and lipoxygenase enzymes (Addy and Burka, 1988); the increase of the prostaglandin synthesis, PGE2 and PGF2a; the opening of the BKCa channels (McManus et al, 1993); or the inhibition of cytochrome P450 NADPH-dependent arachidonic acid metabolism (Addy and Schwartzman, 1992). It inhibits contraction of the guinea pig's ileum and airways (Addy and Awumey, 1984;Burka, 1988, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been carried out to verify if the plant relaxes smooth muscle and to understand better its action. It has been suggested that the action mechanism of the plant is due to the depletion of the HST stocks (Addy and Awumey, 1984); the inhibition of the cyclooxygenase and lipoxygenase enzymes (Addy and Burka, 1988); the increase of the prostaglandin synthesis, PGE2 and PGF2a; the opening of the BKCa channels (McManus et al, 1993); or the inhibition of cytochrome P450 NADPH-dependent arachidonic acid metabolism (Addy and Schwartzman, 1992). It inhibits contraction of the guinea pig's ileum and airways (Addy and Awumey, 1984;Burka, 1988, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been carried out to assess if the plant relaxes smooth muscles and to understand better its action (Addy and Awumey, 1984;Addy and Dzandu, 1986;Addy and Burka, 1987, 1988, 1989, 1990Addy, 1992;McManus et al, 1993;Addy and Schwartzman, 1995;Barreto, 2002).…”
Section: Effect On Smooth Muscles/antiasthmaticmentioning
confidence: 99%
See 1 more Smart Citation
“…A skeletal muscle-relaxant effect was also described ex vivo and in vivo for a Baphia nitida ethyl acetate extract (Adeyemi et al, 2006). More interestingly, three fractions isolated from an aqueous extract of Desmodium adscendens were shown to inhibit allergic airway smooth muscle contraction at multiple sites, including the synthesis and/or activity of the bronchoconstrictor leukotrienes (Addy and Burka, 1988).…”
Section: Mechanism Of the Relaxant Effect Of Etoh/h 2 O Extract Of DImentioning
confidence: 91%
“…For example, in Ghana, the plant decoction is prescribed by healers to treat asthma and other diseases associated with smooth-muscle contraction (13). This characteristic of D. adscendens has been proved to inhibit contraction of the guinea pig's ileum and airways (1)(2)(3). In addition, its traditional use in hepatic affection, particularly viral hepatitis (16), and anti-allergic effects in vivo (3,4) were verified.…”
Section: Introductionmentioning
confidence: 90%